The Effectiveness of the Landa Model on the Development of Innovative Thinking Skills and the Acquisition of Jurisprudential Concepts Among the Students of the Tenth Grade in Jordan - Al- Maqosi, Yaseen Ali (Arab Journal for Sciences and Research Publishing, 2021)
The study aimed to measure the effectiveness of the Landa model in developing innovative thinking skills and gaining the jurisprudential concepts among the students of the tenth grade in Jordan. The study sample consisted of (61) female in Arjan Secondary School for Girls in the Directorate of Education of Amman, in the second semester of the academic year 2019- 2020. The study adopted the experimental method, through distributing students into an experimental group consisting of 30 female students who studied the concepts of jurisprudence according to the Landa model, and a group of 31 female students who studied jurisprudence concepts according to the conventional method. In addition, the researcher applied two tools: the innovative thinking scale, and an achievement test. The results of the study showed statistically significant differences between the total average of the experimental group and the control group in the innovative thinking skills and the achievement test, and in favor of the experimental group who studied according to the Landa model. In view of the study’s result, the study recommended the necessity of holding training courses for Islamic education teachers to employ Landa model in teaching Islamic education.